Severe lacerations in alpine ski racing: A case series and review of the literature - Holden, W. M.; Barnum, M. S.; Tarka, M. C.; Niederhauser, C. A.; Jewell, R. P.; Endres, N. K. (Sports Health: A Multidisciplinary Approach, 2023)
Lacerations in alpine ski racers caused by the sharp metal edge of the ski are potentially severe and even life-threatening injuries. To date, there has been little published on these injuries. This case series reports on 5 cases of severe lacerations in alpine ski racers and details slope side management, initial evaluation, and definitive treatment. By publishing this case series, it is hoped to promote further investigation into the mechanism of these injuries and strategies for prevention.